Diet during pregnancy: Influence of social characteristics and migration in the ELFE cohort - Manik Kadawathagedara; Namanjeet Ahluwalia; Marie‐Noelle Dufourg; Anne Forhan; Marie Aline Charles; Sandrine Lioret; Blandine deLauzon‐Guillain (Wiley, 2021)
Abstract Better adherence to dietary guidelines during pregnancy is supposed to result in healthier perinatal outcomes. We aim to characterize the diets of pregnant women by hypothesis‐driven and exploratory approaches and describe potential social determinants. Analyses included 12 048 mothers from the French nationwide ELFE birth cohort. Dietary intake over the last three months of the pregnancy was assessed by a food frequency questionnaire. Two hypothesis‐driven scores (the Diet Quality score, based on benchmarks derived from the National Health and Nutrition Program Guidelines, and the PANDiet score, based on nutrient intake) were calculated. Exploratory dietary patterns were also identified by principal component analysis. Multiple linear regressions were used to assess associations of maternal social characteristics with dietary patterns, accounting for the possible effect modification by their migration status. Five dietary patterns were identified: the Western, Balanced, Bread and toppings, Processed products, and Milk and breakfast cereals. Younger maternal age, single motherhood, unemployment and the presence of older children in the household were related to a suboptimal diet during pregnancy. The less acculturated the women were, the healthier and less processed their diets were, independent of their socio‐economic position. Several social determinants of the quality of women's diets were however moderated by their migration status. These findings shed light on the relations between indicators of social vulnerability, such as single motherhood and unemployment, and poorer diet quality. Given the reduced diet quality that accompanies the acculturation process, it is of paramount importance to identify the specific factors or obstacles that affect migrant women in maintaining their diet quality advantage over the majority population.